2017
DOI: 10.5232/ricyde2017.05005
|View full text |Cite
|
Sign up to set email alerts
|

Miedo a la evaluación negativa y autoestima como factores predictivos del rendimiento deportivo: Papel mediador de los estados de ansiedad y autoconfianza. [Fear of negative evaluation and self-esteem as predictors of sport performance: The mediational role of anxiety and self-confidence states].

Abstract: El presente estudió examinó el efecto que ejerce el miedo a la evaluación negativa y la autoestima en la predicción del rendimiento deportivo, examinando la mediación de las variables de estado de ansiedad (cognitiva y somática) y la autoconfianza. Participaron 100 estudiantes (rango de edad = 15-17 años; el 66% eran mujeres) de Educación Secundaria, los cuales disputaron un juego de bádminton en condiciones de baja y alta presión psicológica. Los datos basados en modelos predictivos mediacionales constataron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…There is a predictive relationship between competitiveness, individualism, and fear of negative evaluation. Although there are few studies that examine the fear of negative assessment in sport ( Molina et al, 2014 , 2017 ; Atasoy et al, 2016 ) and PE ( Ridgers et al, 2007 ; Huéscar and Moreno-Murcia, 2017 ), none have directly associated competitiveness and individualism with fear of negative evaluation in the area of PE. However, there are studies ( González et al, 2014 ) in which PE classes are identified as a place for peer recognition and where aspects such as empathy with others, being recognized as a leader, or failing as friend at the pre-adolescent stage becomes vital, which according to Hartmann et al (2010) , can increased levels of anxiety and social fears—characteristics related to the fear of negative evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a predictive relationship between competitiveness, individualism, and fear of negative evaluation. Although there are few studies that examine the fear of negative assessment in sport ( Molina et al, 2014 , 2017 ; Atasoy et al, 2016 ) and PE ( Ridgers et al, 2007 ; Huéscar and Moreno-Murcia, 2017 ), none have directly associated competitiveness and individualism with fear of negative evaluation in the area of PE. However, there are studies ( González et al, 2014 ) in which PE classes are identified as a place for peer recognition and where aspects such as empathy with others, being recognized as a leader, or failing as friend at the pre-adolescent stage becomes vital, which according to Hartmann et al (2010) , can increased levels of anxiety and social fears—characteristics related to the fear of negative evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of school sports, some studies suggest that there is a relationship between fear of negative evaluation, competition, and sports performance, a connection that can occur under two conditions ( Molina et al, 2014 , 2017 ). The first indicates that this fear affects sports performance when this activity takes place in an environment of high psychological pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the correlational analysis reflected a negative association between the two dimensions of anxiety (cognitive and somatic anxiety) and of acceptance, showing that competence was negatively related to somatic anxiety and positively to cognitive anxiety. The papers reviewed showed that the two dimensions of resilience were negatively related to those of anxiety [ 37 , 38 , 54 , 55 ]. Similar studies were conducted in team sports such as handball, basketball, football, and rugby, and found that youth athletes with higher levels of resilience managed to moderate their anxiety levels significantly, recovering or adapting better to threatening situations [ 38 , 41 , 42 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, training has been incorporating techniques to develop skills in the athlete, and achieve better performance (Mantilla, 2019). By way of example, a study by Molina, Chorot and Sandín (2017) with and contextual variables together with internalized (depression), and externalized (behavior) problems. Sportis Sci J, 7 (2), 239-266. https://doi.org/10.17979/sportis.2021.7.2.7365 http://revistas.udc.es/ 241 badminton athletes states that self-confidence is associated with better sports performance due to the management of psychological pressure.…”
Section: Introductionmentioning
confidence: 99%